APLIKASI INVENTARISASI DAN PEMINJAMAN PERALATAN LABORATORIUM PROGRAM STUDI TEKNIK INFORMATIKA PADA POLITEKNIK SEKAYU - Serly Oktarina (Politeknik Sekayu, 2015)
Process management tool at the Laboratory of Informatics Engineering Program at Polytechnic Sekayu still manual, where the lending of equipment still using paper forms. Moreover, in making the report was limited to the use of a computer typing all data existing equipment loan using MS-Word. So that the whole produce timely and accurate reports require a relatively long time and produced a report of incompleteness occurs. The purpose of this Information Systems Development is intended to provide solutions to produce software that can facilitate the work of the Head of the laboratory in managing borrowin laboratory equipment and inventory monitoring. Development of an inventory of laboratory information system using RAD system development method, the programming language used Visual Basic (VB) and MySQL as database container media. From the test results obtained by that application Loan Inventory and Equipment Laboratory Informatics Engineering Program at Polytechnic Sekayuq can work well. So that users can check what items already entered, how the condition of the item, of which the acquisition of such goods as well as anyone who is borrowing the equipment.